ANALISIS PERSEPSI DAN PREFERENSI IBU RUMAH TANGGA TERHADAP PRODUK PANGAN OLAHAN BERBASIS TEPUNG UBI JALAR DALAM MENINGKATKAN KEANEKARAGAMAN PANGAN - DWP, Sucihatiningsih; Sutrasmawati, Endang; SW, Indah Fajarini (JEJAK: Jurnal Ekonomi dan Kebijakan, 2009)
The use of sweet potato powder as the substitution of flour for making cake is expected to decreasethe import of flour and increase the added value of sweet potato. The aims of this study are for knowingwhether housewives prefer flour to sweet potato powder and for knowing what the house wivesÃ¢â¬â¢perceptions of food made of sweet potato powder are. In taking the sample, random sampling isapplied.The sample of the study is 50 housewives in Kota Semarang. Furthermore, descriptive statistic,non-parametric approach and SWOT analysis are used in the study.Keywords: preference and perceptions of food made potato powder